Serotonin and Blood Pressure Regulation - Watts, Stephanie W. (The American Society for Pharmacology and Experimental Therapeutics, 2012)
5-Hydroxytryptamine (5-HT; serotonin) was discovered more than 60 years ago as a substance isolated from blood. The neural effects of 5-HT have been well investigated and understood, thanks in part to the pharmacological tools available to dissect the serotonergic system and the development of the frequently prescribed selective serotonin-reuptake inhibitors. By contrast, our understanding of the role of 5-HT in the control and modification of blood pressure pales in comparison. Here we focus on the role of 5-HT in systemic blood pressure control. This review provides an in-depth study of the function and pharmacology of 5-HT in those tissues that can modify blood pressure (blood, vasculature, heart, adrenal gland, kidney, brain), with a focus on the autonomic nervous system that includes mechanisms of action and pharmacology of 5-HT within each system. We compare the change in blood pressure produced in different species by short- and long-term administration of 5-HT or selective serotonin receptor agonists. To further our understanding of the mechanisms through which 5-HT modifies blood pressure, we also describe the blood pressure effects of commonly used drugs that modify the actions of 5-HT. The pharmacology and physiological actions of 5-HT in modifying blood pressure are important, given its involvement in circulatory shock, orthostatic hypotension, serotonin syndrome and hypertension.